Amber Brown is green with envy - Danziger, Paula, 1944-; Ross, Tony (New York : G.P. Putnam's Sons, 2003)
Fourth-grader Amber Brown must make some important decisions when her mother and Max move their wedding date up and prepare to buy a house together, while her father makes some bad choices of his own.
600
Keywords: Fathers and daughters -- Fiction; Mothers and daughters -- Fiction; Divorce -- Fiction; Custody of children -- Fiction; Moving, Household -- Fiction; Family life -- New Jersey -- Fiction